AB0135 Four-day continuous blood exposure leads to prolonged joint damage in a canine in vivo model, not the cumulative blood load of intermittent exposures. (23rd January 2014) - van Meegeren, M.E.; Roosendaal, G.; Mastbergen, S.C.; Lafeber, F.P.
Abstract : Background: In a canine model, intra-articular blood injections twice a week during 4 weeks resulted in transient damage only (1). Human in vitro studies have shown that there is a threshold for the blood load (duration and concentration) to which cartilage has to be exposed to blood, before cartilage damage becomes irreversible (2). This blood load was probably not reached in vivo in the canine model. Objectives: In this study it was evaluated whether continuous blood exposure is more harmful than intermittent blood exposure in a canine model of knee arthropathy. Methods: Seven dogs received 2 series of 4 daily blood injections (continuous exposure) with 2 weeks in between. Seven other dogs received a total number of 8 intra-articular blood injections intermittently over a 4 week period with at least 1 day in between. Contralateral knees served as controls. Ten weeks after the last injection cartilage matrix turnover and synovial inflammation were evaluated. Results: In the blood-exposed joints of both groups proteoglycan synthesis rate was increased (both p≤0.02), as an attempt to repair cartilage. This mimics early features of joint degeneration. Only in the continuous blood-exposed knees the release of newly formed and total (resident) cartilage matrix glycosaminoglycans (GAGs) was increased (p=0.04 and p=0.01, respectively). Furthermore, in the animals with continuous exposure cartilage GAG content was decreased (p=0.01), and not in the animals with intermittent exposure. Mild synovial inflammation was observed in both groups (both p<0.0001), not different between groups. Conclusions: In contrast to intermittent exposure, a 4-day continuous blood exposure twice in 4 weeks leads to prolonged cartilage damage independent of the level of synovial inflammation. This model is of use to study treatment modalities preventing blood-induced arthropathy. References: Hooiveld, M., et al., Blood-induced joint damage: longterm effects in vitro and in vivo. J Rheumatol, 2003. 30(2): p. 339-44. Jansen, N.W., et al., Exposure of human cartilage tissue to low concentrations of blood for a short period of time leads to prolonged cartilage damage: an in vitro study. Arthritis Rheum, 2007. 56(1): p. 199-207. Disclosure of Interest: None Declared